2011
DOI: 10.1007/s00231-011-0931-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of water transport in roof tiles by removal of moisture at isothermal conditions

Abstract: The main objective of this article is to describe the drying process of ceramic roof tiles, shaped from red clay, using diffusion models. Samples of the product with initial moisture content of 0.24 (db) were placed inside an oven in the temperatures of 55.6, 69.7, 82.7 and 98.6°C; and the data of the drying kinetics were obtained. The analytical solutions of the diffusion equation for the parallelepiped with boundary conditions of the first and third kinds were used to describe the drying processes. The proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 31 publications
1
35
0
2
Order By: Relevance
“…However, in this case, a simpler model may be more efficient to describe the drying kinetics. Therefore, it should be pointed out that, according to Silva et al (2012), for such a low Biot number, the infinite series that represents the solution of the diffusion equation can be represented only by its first term, with negligible truncation error. In this case, this first term can be interpreted as the Henderson-Pabis equation, e.g.…”
Section: Description Of Diffusion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case, a simpler model may be more efficient to describe the drying kinetics. Therefore, it should be pointed out that, according to Silva et al (2012), for such a low Biot number, the infinite series that represents the solution of the diffusion equation can be represented only by its first term, with negligible truncation error. In this case, this first term can be interpreted as the Henderson-Pabis equation, e.g.…”
Section: Description Of Diffusion Modelmentioning
confidence: 99%
“…It should be noted that the highest truncation error of the infinite series given by Equation (2) occurs for t = 0, and this error depends on the Biot number referring to drying (Silva et al, 2012). In order to define the number of terms (nt) to be used in Equation (2), the study of Silva et al (2012) was taken into consideration. These researchers observed that, for Bi = 0.001, only 1 term is necessary to obtain X * (0) = 1.0, which is the expected value.…”
Section: Diffusion Modelmentioning
confidence: 99%
“…Moreover, models involving convective boundary condition is better to describe the drying process of tiles, since there is always resistance to mass flow on the surface of the product [19]. Various studies adopt the convective boundary condition for the description of drying processes [3,20,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported in literature using a diffusion model to describe the physical process, and consider the geometric shape of the bodies as cylinder, sphere, or infinite slab [7][8][9][10][11]. Analytical and numerical solutions to predict heat and mass diffusion in porous bodies are also reported for prolate and oblate spheroids [12,13], as well as parallelepipeds [14][15][16].…”
Section: Introductionmentioning
confidence: 99%